The university brand as a factor in attracting applicants - I. I. Cherkasova; V. V. Cherkasov; A. V. Cherkasov (Образование и наука)
Introduction. Today, the competition in educational market is increasing. A wide range of online courses with a simultaneous tendency decrease the interest of schoolchildren in higher education. This aggravates the competition of universities for the attraction of talented applicants. One of the factors, allowing the university to get an advantage when a student chooses a place of study is a recognisable brand, which includes a certain set of associations and characteristics perceived by the students, defined as a brand personality.Aim. The present research aims to identify the factors of the brand personality of Russian universities and to develop a brand personality model as a tool for its evaluation.Methodology and research methods. The research was conducted among students and their parents; 414 people took part at different research stages. A free association test was used to determine a set of characteristics describing the brand personality of Russian universities. Using the results, a list of 22 traits describing the university as a “person” was generated through comparative and content analysis. The development of the brand personality model of Russian universities was carried out on the basis of mathematical and statistical methods.Results. The effectiveness of the developed model for assessing the brand personality of Russian universities, which can be used to attract applicants, has been proved using the methods of mathematical statistics. The methodology for assessing brand individuality was adapted on the example of a pedagogical university. This methodology is a tool for assessing brand personality, which allows comparing, and classifying different universities and getting feedback on the university brand perception by potential applicants. The paper shows the difference of traits characterising Russian and foreign universities. The differences between these groups in the perception of brand personality have been highlighted based on the comparison of students’ and their parents’ brand perception. It is proved that the concept of brand personality can significantly supplement the official measured parameters of university brand success. It is shown that the developed model can be used for communication with applicants, it allows to see the differences of one university from another, translates the values of the university, forms its vision of the target audience.Scientific novelty. The scientific novelty of the study is in the fact that the difference in the applicants' and parents' perceptions of the characteristics of Russian universities in comparison with foreign universities is confirmed. The brand personality model of Russian universities has 20 characteristics united in 4 factors: serious, kind, young, and bright. The developed model allowed the authors to compare and classify universities.Practical significance. The developed model of the brand personality of Russian universities and the adapted methodology of its assessment can be used by universities to obtain feedback, to compare the characteristics of the brand by its developers and features of its perception by the target audience, as well as to compare themselves with competitors. This, in turn, will make it possible to develop marketing strategy for attracting talented applicants.